SOME ISSUES OF DEVELOPMENT AND TERRITORIAL ORGANIZATION OF ECREATION WITHIN THE MOUNTAINOUS TERRITORIES OF UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
The article examines some geographical aspects of the development of tourism and recreation withinmountainous areas. Also, based on available theoretical and practical information, directions, conclusions andrecommendations for the socio-economic development of mountainous areas are given.